Genome Wide Association Study (GWAS) between Attention Deficit Hyperactivity Disorder (ADHD) and Obsessive Compulsive Disorder (OCD) - Ritter, McKenzie L.; Guo, Wei; Samuels, Jack F.; Wang, Ying; Nestadt, Paul S.; Krasnow, Janice; Greenberg, Benjamin D.; Fyer, Abby J.; McCracken, James T.; Geller, Daniel A.; Murphy, Dennis L.; Knowles, James A.; et al. (Frontiers in Molecular Neuroscience, 2017)
Objective: The aim of this study was to identify any potential genetic overlap between attention deficit hyperactivity disorder (ADHD) and obsessive compulsive disorder (OCD). We hypothesized that since these disorders share a sub-phenotype, they may share common risk alleles. In this manuscript, we report the overlap found between these two disorders. Methods: A meta-analysis was conducted between ADHD and OCD, and polygenic risk scores (PRS) were calculated for both disorders. In addition, a protein-protein analysis was completed in order to examine the interactions between proteins; p-values for the protein-protein interaction analysis was calculated using permutation. Conclusion: None of the single nucleotide polymorphisms (SNPs) reached genome wide significance and there was little evidence of genetic overlap between ADHD and OCD.